COMPARISON OF THE CONVENTIONAL BIOCHEMICAL TESTS RECOMMENDED FOR THE IDENTIFICATION OF ESCHERICHIA COLI IN WATER, IN REPORT 71, WITH THE API 20E SYSTEM - M.K. Sharifi-Yazdi; C. Azimi (Tehran University of Medical Sciences, 1998)
The API 20E technique for identification of E.coli was evaluated and the results compared with those obtained by the conventional biochemical tests recommended in Report 71. The results obtained showed very close correlation between the two methods. A total of 196 (81.6%) out of 240 isolates were identified as E.coli by API. System, while the conventional method identified only 194 (80.8%). Therefore the recommended tests in Report 71, which are based on very small number of data was found to be acceptable for the identification of E.coli. The results also showed that, all the colonies showing the typical green metallic sheen on EMB agar are not always E.coli, although all the E.coli showed typical green metallic sheen colonies on EMB agar.